Programming cellular condensates for living materials using an intrinsically disordered protein display platform - Rong Chang; Hann X. Tu; Hongyu Ma; Neel S. Joshi (Proceedings of the National Academy of Sciences, 2025)
Self-organization underpins the emergence of complex structure in living systems but remains a major challenge for engineering synthetic multicellular materials. Here, we present intrinsically disordered protein display platform (iDP 2 ), a generalizable platform for high-density display of intrinsically disordered proteins (IDPs) on the surface of Escherichia coli . iDP 2 uses CsgF as a surface-tethered scaffold, enabling efficient fusion and presentation of protein domains that lack stable tertiary structure. Successful display selectively favors disordered sequences, which, when endowed with phase separation propensity, drive the formation of dynamic cellular condensates. Programming cells with orthogonal IDPs enables sequence-specific segregation of mixed populations, allowing the design of spatially organized living assemblies. The aggregation state of these condensates is dynamically tunable by environmental cues such as ionic strength, and temperature, with responses predictable from the known phase behavior of the displayed IDPs. Extrusion processing of condensates generates macroscale filaments that maintain structural integrity and population segregation. By linking protein sequence to emergent collective behaviors, iDP 2 offers a programmable framework for rational control of cell–cell interactions. This approach establishes a foundation for engineering living materials with customizable viscoelastic properties, environmental responsiveness, and multicellular organization. More broadly, our work highlights the potential of disordered protein motifs as versatile tools for the design of adaptive, self-organizing biological systems.